2014
DOI: 10.14712/18059694.2014.46
|View full text |Cite
|
Sign up to set email alerts
|

Crohn’s Disease: a Role of Gut Microbiota and Nod2 Gene Polymorphisms in Disease Pathogenesis

Abstract: Crohn’s disease is a chronic immune-mediated intestinal inflammation targeted against a yet incompletely defined subset of commensal gut microbiota and occurs on the background of a genetic predisposition under the influence of environmental factors. Genome-wide association studies have identified about 70 genetic risk loci associated with Crohn’s disease. The greatest risk for Crohn’s disease represent polymorphisms affecting the CARD15 gene encoding nucleotide-binding oligomerization domain 2 (NOD2) which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 99 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…Relations of NOD/CARD system and other gut disorders is also confi rmed by the results of Hrnčířová et al [71] concerning distinct associations between Crohn's disease and some gene variants of CARD15/NOD2 gene.…”
Section: Other Human Genes Potentially Changing Gut Microbiotamentioning
confidence: 63%
“…Relations of NOD/CARD system and other gut disorders is also confi rmed by the results of Hrnčířová et al [71] concerning distinct associations between Crohn's disease and some gene variants of CARD15/NOD2 gene.…”
Section: Other Human Genes Potentially Changing Gut Microbiotamentioning
confidence: 63%
“…Importantly, the early finding of a defect in the caspase recruitment domain family, member 15 ( NOD2/CARD15 ) gene among CD patients, has reawakened the search for specific involved pathogens [28]. NOD2/CARD15 is involved in the innate immune system including the production of defensins; therefore, defects in this gene could imply that the host is more susceptible to gastrointestinal infections [29]. It has, furthermore, been shown that the number of viable internalized Salmonella typhimurium in Caco‐2 cells was higher when the Caco‐2 cells were transfected with a variant CARD15/NOD2 expression plasmid associated with Crohn's disease [30].…”
Section: Introductionmentioning
confidence: 99%